SOCIAL INCLUSION OF WOMEN IN INDIAN ADVERTISING - Singh, Vishwajit (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Contemporary Indian advertising is increasingly indulging in the ever more prominent and gripping concerns of societal development, making themselves active participants in empowering women. This paper explores the significance of video and press advertising as a media serving to transform and bring about some crucial changes in concepts and issues related to women’s equality, diversity, and inclusivity in society. Our society’s age-old projections of the role played by women are sensitive and hold a pertinent concern for the welfare of humanity. Social inclusion is a global dimension that directly impacts the development of our culture, making it an ever more concerning subject dealing with utmost integrity, sincere support, and a holistic approach. The result of this change in our environment may not be immediate, but its significance is gaining rapid recognition and a firm grasp of the psychological roots of people. Advertisements projecting women through equality and inclusivity also give a critical overview. Still, the lead to encouragement is that social inclusion is a need for social diversity, specifically in a country like ours, where the all-inclusive identity of its diverse cultures represents the nation as one. The contribution of advertising as a distinct field in this process is accelerating at a reasonable rate, offering several brands, companies, and services to present themselves to society within the framework of inclusivity perspectives.